2020
DOI: 10.1007/s11166-020-09336-3
|View full text |Cite
|
Sign up to set email alerts
|

Political polarization in US residents’ COVID-19 risk perceptions, policy preferences, and protective behaviors

Abstract: When the novel coronavirus entered the US, most US states implemented lockdown measures. In April–May 2020, state governments started political discussions about whether it would be worth the risk to reduce protective measures. In a highly politicized environment, risk perceptions and preferences for risk mitigation may vary by political inclinations. In April–May 2020, we surveyed a nationally representative sample of 5517 members of the University of Southern California’s Understanding America Study. Of thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
161
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(205 citation statements)
references
References 28 publications
14
161
0
Order By: Relevance
“…Throughout the pandemic, COVID-19 risk perception and mitigation have been discussed and explored via a variety of national polls and studies keeping in mind sociodemographic factors and political affiliation [ 17 , 18 , 24 , 27 ]. For example, the wearing of face masks became a divisive issue and ended up becoming a “culture war” with a greater divide in compliance based on gender, age, and political affiliation [ 24 , 27 ]. Even while the trials for the COVID-19 vaccine were going on worldwide, many Americans did not believe COVID-19 was a serious problem or the topmost concern in the country.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout the pandemic, COVID-19 risk perception and mitigation have been discussed and explored via a variety of national polls and studies keeping in mind sociodemographic factors and political affiliation [ 17 , 18 , 24 , 27 ]. For example, the wearing of face masks became a divisive issue and ended up becoming a “culture war” with a greater divide in compliance based on gender, age, and political affiliation [ 24 , 27 ]. Even while the trials for the COVID-19 vaccine were going on worldwide, many Americans did not believe COVID-19 was a serious problem or the topmost concern in the country.…”
Section: Discussionmentioning
confidence: 99%
“…Even while the trials for the COVID-19 vaccine were going on worldwide, many Americans did not believe COVID-19 was a serious problem or the topmost concern in the country. Republicans, Democrats, and other participants in polls and studies differed in their opinion with certain groups less likely to believe in the seriousness of COVID-19, the efficacy of masks, scientific guidance on controlling the pandemic, and willingness to take a COVID-19 vaccine when it became available [ 4 , 6 , 17 , 18 , 24 , 27 ]. To reach the levels of reasonable herd immunity or for successful mass COVID-19 immunization, tailored and community-based interventions that can address the political divide and risk perception differences will be needed along with the plans to distribute the COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used data collected in the American Community Survey (ACS) (U.S. Census Bureau, 2019) to estimate county-level household income as well as income inequality. We included political leanings in our model because, in a survey of more than 5,000 individuals, de Bruin et al (2020) found that self-identified Democrats were more likely to cancel planned air travel in response to concerns of COVID-19. This behavior suggests that personal politics could indicate changes in air travel patterns.…”
Section: Analysis Of Closed Airportsmentioning
confidence: 99%
“…Perceptions of the COVID‐19 risk and the efficacy of precautions are strongly correlated with political beliefs (de Bruin et al . 2020). For some, individual freedom is an absolute right that can never be compromised.…”
Section: Values That Cannot Be Compromisedmentioning
confidence: 99%